The ballad of Jacquotte Delahaye : a novel - Cameron, Briony (Atria Books, 2024)
"An epic, dazzling tale based on true events, The Ballad of Jacquotte Delahaye illuminates a woman of color's rise to power as one of the few purported female pirate captains to sail the Caribbean, and the forbidden love story that will shape the course of history"--